129 "Pop-Up" Specialist End of Life Ward For COVID-19—The Nottingham Experience. (16th March 2021) - Arnott, R; Lewis, A; Berbecila, D; Deery, J; Wells, L; Poon, M H
Abstract: Background: Our hospital trust anticipated an increased need for palliation and end of life care (EoLC) in patients with Covid-19 who were not appropriate for escalation and mechanical ventilation. Intervention: A dedicated ward was opened as part of the trust-wide Covid-19 admissions pathway, led by geriatricians with palliative care input and staffed by relocated nursing and auxiliary personnel. Retrospective data was collected for consecutive patients admitted to the ward between 3rd April and 26th May 2020 and qualitative data regarding staff experience using a questionnaire. Result: Of the 168 patients (55% male) admitted, 31.5% came directly from Emergency Department, 17.3% from admission areas and the remainder from inpatient wards. Time spent on the ward ranged from 10 minutes to 17 days (median length of stay 43 hours). 75% had Clinical Frailty Scale score of 6 or more. 150 died with 75% naming Covid-19 as primary cause or contributing factor. Ward staff, who were not palliative care specialists, reported increased confidence in many aspects of palliation including assessing comfort, relieving symptoms, prescribing and administering anticipatory medications and in supporting and communicating with relatives. Staff apprehension about working on a Covid ward eased once the ward was established. Qualitative themes emerging from staff feedback included: professional competency, communication, prioritisation, team work, emotional response, care and consistency in a time of change. Discussion: The pathway and referral system ensured that our ward cared for appropriate older patients living with frailty. The formation of a specialist unit over a short period of time created a series of logistical and management challenges. The emotional burden felt by staff was also prominent in feedback. These challenges were outweighed by the personal and professional development of staff coupled with the strong sense of teamwork, pride and enthusiasm felt in providing high quality care.